Macroeconomic Drivers of Inflation in Ethiopia: Evidence from ARDL Modeling - Betselot Adisu Ayal; Mekuanent Alemu Amanu; Kassa Yirga Bekalu; Mullugeta Molla Ayenalem (EkBis: Jurnal Ekonomi dan Bisnis, 2025)
Despite ongoing macroeconomic reform and liberalization measures, inflation remains a critical and persistent problem in Ethiopia. Persistent inflation poses a grave threat to the country's status and economic stability. Thus, this study aimed to investigate the macroeconomic factors driving inflation in Ethiopia employing the ARDL model using annual data for the period 2012–2023. The NBE, EEA, IMF, and WB provided the macroeconomic variable data. The unit root test was employed to determine the variables’ order of integration and ADF and PP tests revealed that all series are non-stationary while stationary at the first difference. The study's findings indicated that money supply growth, import value to GDP ratio, budget deficit, and public expenditure all have a positive and statistically significant impact on inflation in both the long and short run. Lending interest rates, which are inflationary in the short run, have a deflationary effect in the long run. On the other hand, the external debt to GDP ratio, official exchange rate, and growth rate of real GDP are found to have significant negative effects on inflation in the long run. In the short run, the external debt-to-GDP ratio has a negative but insignificant impact on the determinates of inflation. Meanwhile, the real domestic product's growth rate significantly lowers inflation in the short run. The study recommends that a broad money supply is to be controlled and gross national saving is to be encouraged to reduce inflation in the country.